Nonnative Speakers Do Not Take Competing Alternative Expressions Into Account the Way Native Speakers Do. Issue 1 (26th October 2015) - Robenalt, Clarice; Goldberg, Adele E.
Abstract: When native speakers judge the acceptability of novel sentences, they appear to implicitly take competing formulations into account, judging novel sentences with a readily available alternative formulation to be less acceptable than novel sentences with no competing alternative. Moreover, novel sentences with a competing alternative are more strongly dispreferred when they contain high‐ compared to low‐frequency verbs. We replicate these findings with a group of native speakers and extend the paradigm to second language (L2) users. Previous work has found that compared to native speakers, L2 users are less able to generate online expectations during language processing, implying a reduced ability to differentiate between novel sentences with and without a competing alternative. We test this prediction and confirm that, while L2 speakers learn from positive exemplars, they show no evidence of taking competing grammatical alternatives into account, except at the highest quartile of speaking proficiency, where L2 judgments align with native speaker judgments. Open Practices: This article has been awarded Open Materials and Open Data badges. All materials and data are publicly accessible via the Open Science Framework athttps://osf.io/f3dh6 . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .